Психологічні аспекти впливу соціальних мереж на підлітків - Ольховська, В. О. (ХНУРЕ, 2021)
This article discusses the relationship between social media use and adolescent psychological health. The Internet and social media play a significant role in the lives of young people, with both positive and negative consequences. The relevance of this article is associated with the increasingly widespread dissemination of technologies, gadgets, various media resources, and, as a result, the increasingly widespread influence on adolescents. Both the positive and harmful effects of social media were analyzed. It is important to preserve the psychological well-being of adolescents, reduce the risks associated with psychological addiction, and enhance the positive effect.
Keywords: філософія; вплив соціальних мереж на підлітків